Performance analysis of direct solar dryer driven by photovoltaic thermal energy recovery and solar air collector for drying materials and electricity generation. Issue 4 (7th February 2022) - Kabeel, A. E.; El‐Sheekh, Mostafa M.; Masoud, Alaa A.
Abstract: The direct‐type solar dryer is characterized by very simple construction, less maintenance, cost‐effectiveness, and is easy to handle. The present study aims to enhance the performance of a direct‐type solar dryer. To achieve this, the photovoltaic (PV) panels with thermal energy recovery and solar air collector were integrated with the direct‐type solar dryer. In this study, the PV panels with thermal energy recovery and solar air collector were utilized as preheating units to raise the air temperature before entering the direct solar dryer. Moreover, the PV panels were utilized to drive the air blower. In this study, three incorporated models are suggested to study the performance of the solar dryer integrated with PV panels with thermal energy recovery and solar air collector. The model of each component was validated by the previously recorded empirical data. The results confirmed that the dual utilization of the PV panels with thermal energy recovery and solar air collector as a preheating unit raised the air temperature entering the direct solar dryer by the rate varying between 29°C and 42°C within the period 9:00 a.m.–4:00 p.m. Also, the moisture content of banana samples inside the direct solar dryer reduced from the initial value of 72% (wb) to the value of 33.4% (wb) within 7 h (9:00 a.m.–4:00 p.m.). During this operating period, moisture removal from the banana samples varied between 110 and 400 g/h.